2015
DOI: 10.1186/s12969-015-0013-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of a pediatric rheumatology transition program

Abstract: BackgroundTransition from pediatric to adult care can be a challenging process which leaves young people vulnerable to interruptions of care and worsening disease status. Efforts to improve transition processes and outcomes have included development of individualized transition plans, creation of transition clinics, and utilization of transition coordinators. Few interventions have assessed transition outcomes quantitatively.MethodsWe assessed transition outcome and satisfaction of a social worker-centered tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 35 publications
1
34
0
1
Order By: Relevance
“…Policies and protocols should be agreed with all major stakeholders, including YP, families and all healthcare professionals and as equal partners;27 33 35 it is important to stress the need to include all specialists (and not just in rheumatology) and primary care physician(s) who are involved in the clinical care of YP with jRMD28 Hospital or institutional managers will have to agree to these policies to facilitate appropriate resources to support their implementation within the clinical departments. As a minimum, there must be a transition policy and the documents should be updated at least every 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…Policies and protocols should be agreed with all major stakeholders, including YP, families and all healthcare professionals and as equal partners;27 33 35 it is important to stress the need to include all specialists (and not just in rheumatology) and primary care physician(s) who are involved in the clinical care of YP with jRMD28 Hospital or institutional managers will have to agree to these policies to facilitate appropriate resources to support their implementation within the clinical departments. As a minimum, there must be a transition policy and the documents should be updated at least every 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…9 Although these studies found positive short-term health outcomes (better glycosylated haemoglobin (Hb1Ac) levels and less short-term complications) and follow-up rates, there is currently no evidence for (long-term) outcomes of TCs with regard to health outcomes, healthcare use, self-management and psychosocial functioning of young adults. Moreover, recent studies of TCs in other diagnostic groups did not include a controlled pre-post outcome evaluation, [19][20][21][22][23][24][25][26][27][28][29][30] and as such could not provide sound evidence on outcomes of TCs. In general, there is inconclusive evidence considering the effectiveness of transitional care.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of transition has also been described in paediatric patients with other chronic diseases with success varying from 42 to 53% of patients . All these studies used a restricted definition of success, namely attending the first one or two visits in adult care.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, a ranking list with key elements and indicators of successful transition in general was published . This list, together with previous literature, supports the elements of the Transition Yourself Score . A qualitative evaluation by the patient was included because patient experiences are of essential importance, reflect continuity of care and should be taken into account .…”
Section: Discussionmentioning
confidence: 99%